Golay Code Excitation of Ultrasonic Transducers with Different Backing - SECOMSKI, Wojciech; TROTS, Ihor; NOWICKI, Andrzej (Archives of Acoustics, 2008)
Two 3.7 MHz focused ultrasonic transducers were built. One without backing and thesecond loaded on back. The primary application of the first transducer is Doppler blood flowmeasuring ultrasonic devices, the second is most useful for the B-mode imaging devices. Theelectrical and acoustical properties were tested and finally the results of the different Golaycode excitations were compared. Efficiency of the not backed transducer was 4.1 dB higher.The not backed transducer performed maximum sensitivity for 8 bit two periods per bit codeexcitation. The backed transducer achieved maximum axial resolution for 16 bit one periodper bit excitation.